Avaliação de parâmetros clínicos, salivares e moleculares em pacientes com síndrome de Down - Castilho, Aline Rogéria Freire de (2007)
There is a need for a better understanding of the factors that affect the development of dental caries in Down syndrome. Thus, the aim of this study was 1) to determine the occurrence of dental caries using DMFT, DMFS, dmft and dmfs indexes, 2) to evaluate the salivary profile by flow rate and buffering capacity, 3) to determine the number of colonies forming units of mutans streptococci (CFU/mL) in saliva, 4) and to assess the prevalence of Streptococcus mutans and Streptococcus sobrinus by polymerase chain reaction. The experimental group included 60 individuals with Down syndrome of both genders and aged one to 48 years old. The mean values of caries indexes were DMFT=4.53, DMFS= 6.85, dmft= 1.55 and dmfs= 2.55. Ninety-four percent of individuals had low flow rate and 6.0% had normal flow rate. Forty-four percent had low buffering capacity, 39.0% had limited buffering capacity, and 17.0% had normal buffering capacity. Besides, 60.0% had more than 1x106 CFU/mL in saliva. Almost all individuals (69.0%) had S. mutans in saliva, 41.4% had S. sobrinus and 17.3% had no S. mutans or S. sobrinus in the mouth. The data were statistically analyzed by chi-square and Pearson s correlation (X= 0.05). There was a significant positive correlation between DMFT or DMFS and age (r= 0.80; p< 0.01; r= 0.82; p< 0.01, respectively) by Pearson s correlation. Nevertheless, caries indexes did not significantly correlate with flow rate, buffering capacity, and number of colony forming units (p>0.05). A chi-square test showed no significant association of DMFT, DMFS, dmft and dmfs indexes with the prevalence of S. mutans and S. sobrinus in the mouth or with gender (p>0.05). These findings show that there is no association between clinical picture and salivary or molecular parameters in Down syndrome individuals.